Respuesta :

Answer:

The answer is the option A

[tex](4,6)[/tex]

Step-by-step explanation:

we have

[tex]4x=3y-2[/tex] -----> equation A

[tex]18=3x+y[/tex] ----> isolate the variable y

[tex]y=-3x+18[/tex] -----> equation B

Substitute the equation B in the equation A

[tex]4x=3(-3x+18)-2[/tex]

[tex]4x=-9x+54-2[/tex]

[tex]4x+9x=52[/tex]

[tex]13x=52[/tex]

[tex]x=4[/tex]

substitute the value of x in the equation B

[tex]y=-3(4)+18=6[/tex]

therefore

the solution is the point [tex](4,6)[/tex]